Soil Seed Bank Persistence Across Time and Burial Depth in Calcareous Grassland Habitats - Mašková, Tereza; Poschlod, Peter (Frontiers in Plant Science, 2022)
Seed persistence in the soil is crucial for population dynamics. Interspecific differences in soil seed mortality could be a mechanism that may stimulate species coexistence in herbaceous plant communities. Therefore, understanding the levels and causes of seed persistence is vital for understanding community composition and population dynamics. In this study, we evaluated the burial depth as a significant predictor of the temporal dynamics of soil seed persistence. We suppose that species differ in this temporal dynamics of soil seed persistence according to burial depth. Furthermore, we expected that burial depth would affect soil seed persistence differently concerning the species-specific type of dormancy, light, and fluctuating temperature requirements for germination. Seeds of 28 herbaceous species of calcareous grasslands were buried in the field into depths of 1, 5, and 10 cm under the soil surface. Seed viability was tested by germination and tetrazolium tests several times for three years. Species-specific seed traits - a type of dormancy, light requirements and alternating temperature requirements for germination, and longevity index - were used for disentangling the links behind species-specific differences in soil seed persistence. Our study showed differences in soil seed persistence according to the burial depth at the interspecific level. Generally, the deeper the buried seeds, the longer they stayed viable, but huge differences were found between individual species. Species-specific seed traits seem to be an essential determinant of seed persistence in the soil. Seeds of dormant species survived less and only dormant seeds stayed viable in the soil. Similarly, seeds of species without light or alternating temperature requirements for germination generally remained viable in the soil in smaller numbers. Moreover, seeds of species that require light for germination stayed viable longer in the deeper soil layers. Our results help understand the ecosystem dynamics caused by seed reproduction and highlight the importance of a detailed long-term investigation of soil seed persistence. That is essential for understanding the fundamental ecological processes and could help restore valuable calcareous grassland habitats.